20th IEEE/NPSS Symposium onFusion Engineering, 2003.
DOI: 10.1109/fusion.2003.1426618
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of cyanate ester resin

Abstract: Traditional epoxy resin systems have long been used for vacuum impregnation of large electro-magnets. However, the mechanical strength of these systems is disappointingly low when operated at temperatures above about 7O0C where the failure mechanism is more often by adhesion at the copper interface than by cohesion within the resin. A range of resin systems based on cyanate ester are currently being developed by CTD Inc. which are suitable for vncuum impregnation and may offer advantages over the epoxy resin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…When compared with the PU adhesive neat system, the LSS for the blends of PU-CER with PU system was almost doubled at ambient and high temperatures for both MS-MS and Al-Al, possibly due to the secondary forces of hydrogen bonding and dipole-dipole interaction of cyanate ester adding more cohesion within the PU adhesive and PU-CER than the adhesion at the MS or Al interface, as stated by Voss et al [11] and also reported by Shimp [16] on the unique properties of thermosetting cyanate ester resins. The toughness-T g combination is attributed to the adhesion strength by ether-like oxygen linkages and relatively low crosslink density.…”
Section: Polyurethane System Blend With Polyurethane Cyanate Resinssupporting
confidence: 53%
“…When compared with the PU adhesive neat system, the LSS for the blends of PU-CER with PU system was almost doubled at ambient and high temperatures for both MS-MS and Al-Al, possibly due to the secondary forces of hydrogen bonding and dipole-dipole interaction of cyanate ester adding more cohesion within the PU adhesive and PU-CER than the adhesion at the MS or Al interface, as stated by Voss et al [11] and also reported by Shimp [16] on the unique properties of thermosetting cyanate ester resins. The toughness-T g combination is attributed to the adhesion strength by ether-like oxygen linkages and relatively low crosslink density.…”
Section: Polyurethane System Blend With Polyurethane Cyanate Resinssupporting
confidence: 53%
“…These could be removed and replaced with the centre column, but are still a critical item since they are so closely coupled to the divertor design. It is suggested that the coil be insulated with cyanate-ester (CE) impregnated glass fibre [28] which has improved radiation resistance compared to conventional epoxy-resins [29]. The gamma flux in the CTF design above is, however, higher than the ITER reference level for coil insulation.…”
Section: Insulating the Divertor Coilsmentioning
confidence: 95%
“…70-100 • C). CE has a (noncompressed) shear stress limit of 40-60 MPa at 100 • C compared to conventional epoxy resins which have dropped to ∼20 MPa at this temperature [28].…”
Section: Insulating the Divertor Coilsmentioning
confidence: 99%
“…The highly stressed solenoid can be allowed to reach 100 , rather than the operational limit of 70 typically applied to epoxy due to its decreasing strength with increasing temperature. The Culham Centre for Fusion Energy (CCFE) has worked for some years with Composite Technology Development (CTD) characterizing the CTD-403 resin [5]. Manufacture of a test coil using conventional industrial techniques and equipment was considered a vital next step in qualifying the material for use on MAST-Upgrade.…”
Section: Introductionmentioning
confidence: 99%